The role of macrophages in oral cancer: A narrative review - Rezhat Abbas; Zeenat Shah; Mohd Musaib Bhat (Saudi Journal of Oral Sciences)
One of the immune cells that are most prevalent in the tumor microenvironment of tumors is the macrophage, and in most malignancies, the macrophage’s presence is correlated with a worse survival rate. Tumor-associated macrophages (TAMs) are the primary cells that generate an immunosuppressive tumor microenvironment by generating cytokines, chemokines, and growth factors, as well as activating the release of inhibitory immunological checkpoint proteins in T cells. The role of TAMs in tumor development will be discussed in this review, covering elements such protumorigenic inflammation, immune suppression, neoangiogenesis, and acceleration of tissue invasion and distant metastasis. Major research databases such as PubMed, Science Direct, Scopus, Web of Science, and Google scholar were explored from 2022 to 2023, yielding 110 papers. Based on the inclusion criteria, this review comprised 30 articles. Macrophages promote angiogenesis, cancer cell invasion, and intravasation at the initial location and are present throughout the whole course of a tumor. Macrophages and monocytes at the metastatic site encourage extravasation and survival of disseminated cancer cells by preventing immune-mediated clearance or by directly interacting with the tumor cells to activate prosurvival signaling pathways. This is done by preparing the metastatic site for the arrival of disseminated tumor cells. A supportive metastatic niche is established by macrophages, which further encourages the proliferation of disseminated cancer cells at the metastatic location. Macrophages have a critical function in tumor progression, affecting the prognosis. Treatments that decrease TAMs and limit their function have been found to be clinically effective. Many diagnostic and therapeutic medications are now available as nanoparticles owing to advancements in nanobiotechnology. TAMs can be employed as nanoparticle carriers in cell therapy to boost the therapies’ tumor-killing ability.